Population Growth in the Border Villages of Srem, Serbia - Lukić, Tamara; Bubalo - Živković, Milka; Đerčan, Bojan; Jovanović, Gordana (Acta geographica Slovenica, 2014)
Population growth in the border villages of Srem (Vojvodina, Serbia) has been analysed in this paper, with the goal of explaining how and why it differed from other areas in the region. Special attention has been paid to the 1990s, because these villages became part of a border region and a high level of migration on the territory of the former Yugoslavia occurred, much of it through this territory. The results of the research are derived from literary resources and applying mathematical and statistical procedures in the processing of data received from the Statistical Office of the Republic of Serbia. They were checked on the field via a questionnaire. This paper is significant because it enriches knowledge about villages of Srem, the municipality of Šid and population trends at the end of the 20th century.